2007
DOI: 10.1159/000110491
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Stress in Patients with Acute Cerebrovascular Events

Abstract: Signs of myocardial involvement are common in patients with acute cerebrovascular events. ST segment deviations, abnormal left ventricular function, increased N-terminal pro-brain natriuretic peptide (NT-proBNP), prolonged QT interval, and/or raised troponins are observed in up to one third of the patients. The huge majority of these findings are fully reversible. The changes may mimic myocardial infarction, but are not necessarily identical to coronary thrombosis. Based on the literature these signs may repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 88 publications
0
22
0
1
Order By: Relevance
“…37 In patients with stroke, cTn is increased approximately 10% and is associated with adverse outcome. 38 Exaggerated catechol-…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…37 In patients with stroke, cTn is increased approximately 10% and is associated with adverse outcome. 38 Exaggerated catechol-…”
Section: Discussionmentioning
confidence: 99%
“…38 In hospitalized non-cardiac patients, potential etiologies for increased cTn include subendocardial damage secondary to increased wall stress, and oxygen supply/demand mismatch. In this study, higher hs-TnT was associated with not only left ventricular hypertrophy and systolic dysfunction, but also the presence of potential comorbidities through cardiac stress.…”
mentioning
confidence: 99%
“…Two previous narrative reviews [9, 10] have commented on the relationship between troponin and stroke. However, neither has included all available studies nor have they used a systematic review approach with meta-analysis, summary statistics and clear end points [11].…”
Section: Introductionmentioning
confidence: 99%
“…Another study reported elevated serum cortisol levels after stroke, and the association of higher concentrations in patients with myocardial damage [17]. Increased catecholamine release has also been proposed to cause the excessive release of intracellular calcium ions, thereby causing myocyte dysfunction [18]. These ndings suggest that a relationship exists between the sympathetic nervous system and myocardial cell damage in ischemic stroke patients.…”
Section: Discussionmentioning
confidence: 97%